(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article analyzes the theoretical and practical foundations of ensuring patient safety-one of the most critical issues in the global healthcare system. Within the framework of the study, a comparative analysis was conducted on the latest accreditation standards, including the Joint Commission International (JCI) 8th Edition (2024) and the National Accreditation Board for Hospitals (NABH) 6th Edition (2025). The paper highlights International Patient Safety Goals (IPSG), medical error reduction strategies, clinical risk management, and the role of digital technologies, such as Artificial Intelligence (AI) and Electronic Medical Records (EMR), in developing a safety culture. Furthermore, the article substantiates the importance of transitioning from a "blame culture" to a "systems analysis culture" within medical institutions. The findings of this research serve as a methodological guide for healthcare administrators, quality managers, and clinical specialists in integrating international standards into national practice.